An improved hybrid nanocomposites of rice husk derived graphene (GRHA)/Zeolitic imidazolate framework-8 for hydrogen adsorption. (13th July 2021) - Arifin, N.F.T.; Yusof, N.; Nordin, N.A.H.M.; Jaafar, J.; Ismail, A.F.; Salleh, W.N.W.; Aziz, F.
Abstract: In this work, hybrid nanocomposites rice husk derived graphene (GRHA) and zeolitic imidazolate framework-8 (ZIF-8) were prepared for hydrogen adsorption. The main contribution of this study is the simplification of the synthesized GRHA/ZIF-8 hybrid nanocomposites. Besides that, the use of synthesized graphene from rice husk (RH) could help in overcoming environmental issue since disposal of RH is rather challenging. GRHA was obtained through calcining rice husk ash (RHA) at 900 °C for 2 h in a muffle furnace at atmospheric condition while the nanocomposite of GRHA/ZIF-8 was produced in free solvent condition using deionized water at room temperature for only 1 h. The N2 adsorption-desorption indicated a type I isotherm. Interestingly, it was found that the BET specific surface area (BETSSA ) of GRHA/ZIF-8 showed enhancement up to 3 times higher as compared to pristine GRHA with the addition of 0.2 g of GRHA. From the experimental data, the adsorption of H2 by nanocomposite GRHA/ZIF-8 obeyed the pseudo-second order kinetic model and intraparticle diffusion model with R 2 value up to 0.9890 and 0.8087 respectively at 12 bar. Moreover, the GRHA/ZIF-8 possessed highest hydrogen adsorption of 31.84 mmol/g at 12 bar. These impressive results are justified by the combination of ZIF-8's microporosity and GRHA's mesoporosity. Highlights: Rice husk derived graphene (GRHA) incorporated zeolitic imidazolate framework-8 (ZIF-8shows an enhanced hydrogen adsorption. GRHA incorporated ZIF-8 (GRHA/ZIF-8) has a higher specific surface area as compared to pristine GRHA and ZIF-8. KOH able to form porosity and increase the surface area of rice husk during the activation process. Hydrogen adsorption capacity increases with time and specific surface area of the adsorbent. The hydrogen adsorption at room temperature obey pseudo-second order model and intraparticle diffusion model.